A Continuous 55 Million Year Record of Transient Mantle Plume Activity Beneath Iceland - Parnell-Turner, Ross; White, Nicky; Henstock, Tim; Murton, Bramley; Maclennan, John; Jones, Stephen M. (Nature Publishing Group, 2014)
In the North Atlantic Ocean, a mid-oceanic ridge bisects the Icelandic mantle plume, providing a window into the temporal evolution of this major convective upwelling 1–3 . It is generally accepted that this plume’s transient behavior is indirectly recorded within the fabric of oceanic ﬂoor south of Iceland 4–7 . Despite its signiﬁcance, the structure of this region is poorly known. Here, we present long seismic reﬂection proﬁles that traverse the oceanic basin between northwest Europe and Greenland. A diachronous pattern of V-shaped ridges is imaged beneath a thickening blanket of sediment, revealing a complete record of transient periodicity that can be traced continuously back to ∼ 55 Myrs— the longest record of its kind. This periodicity increases from ∼ 3 to ∼ 8 Myr with clear evidence for minor, but systematic, asymmetric crustal accretion. V-shaped ridges grow with time and reﬂect small (e.g. 5–30◦ C) ﬂuctuations of mantle temperature, consistent with quasi-periodic generation of hot solitary waves triggered by growth of thermal boundary layer instabilities within the mantle . Our continuous record of convective activity predicts a history of regional elevation change which moderated overﬂow of the Neogene precursor of North Atlantic Deep Water and which controlled the growth and decay of multiple Paleogene buried landscapes.